Guía para la Gestión de los Riesgos Financieros en las Compañias del Sector Primario de la Zona 7 - Cabrera Ponce, Darwin Ramiro (2023)
This Curricular Integration Work called GUIDE FOR THE MANAGEMENT OF FINANCIAL RISKS IN THE PRIMARY SECTOR COMPANIES OF ZONE 7, has been developed with the purpose of helping the administrators of the companies of the economic sector mentioned above, to look for solutions and make decisions to face and mitigate the different financial risks that may arise during the development of their activities, causing delays and even preventing the fulfillment of the proposed objectives. For the development of the first objective, the financial risk factors of the companies in zone 7 of the primary sector were analyzed, taking into consideration the information gathered by the 2009 thesis students (Tamara Alvarado, Martha Montaño and Mary Celi) on the subject: Determination of the factors that affect the dissolution and liquidation of companies by economic sector in the province of El Oro, Loja and Zamora Chinchipe period 2015-2020, who started the research project the previous cycle and taking information from the Superintendence of Companies Securities and Insurance, they elaborated a database where all the companies that were dissolved and liquidated during the period 2015-2020 are presented, achieving through the application of different indicators such as liquidity indicator, indebtedness, leverage and profitability, to know which companies entered the process of dissolution and liquidation, these data were used to analyze and determine the type of financial risk that affected each of the dissolved companies in the primary sector of zone 7. After analyzing the risk factors that caused the cessation of the activities of several companies in this economic sector and after verifying that they did not have a guide to face the different financial risks that were presented to them during the period 2015- 2020, the elaboration of the same is proposed. This guide was made with the purpose of improving the management of financial risks in the companies of the primary sector of zone 7, so that it can be understood by all stakeholders and the suggestions presented can be applied by the administrators of the companies that make up this productive sector.